How do open space characteristics influence open space use? A study of Melbourne's Southbank Promenade. Issue 1 (1st January 2020) - Wang, Zhugen; Stevens, Quentin
ABSTRACT: With the importance of open spaces to urban quality of life being increasingly recognized, knowledge about which spatial characteristics influence open space use, how, and why is of growing interest to open space researchers, designers and managers. Through an observational survey of Southbank Promenade in Melbourne, Australia, the research examines how various specific design characteristics of open spaces correspond to their actual uses. The findings show that different levels and kinds of uses are associated with the different space features of three distinct sections of Southbank Promenade, under varying time and weather conditions.